Leveraging informal markets for health and nutrition security - Alonso, Silvia; Domínguez Salas, Paula (Elsevier, 2019)
Functioning food value chains are essential to assuring health and food security. In low- and middle-income countries, informal food markets, or traditional value chains, are the most important source of food for the largest part of the population, in particular the poor. Leveraging such value chains is essential to offering consumers in those country healthy and nutritious food options that are affordable, acceptable and preferred. The chapter discusses the contribution of informal markets to food and nutrition security and present options to leveraging the steps along the value chain to contribute to improve food security, nutrition and health.